Aberrant ICOS+‐T cell differentiation in women with spontaneous preterm labor. (21st September 2016) - Kälble, Florian; Mai, Charlotte; Wagner, Miriam; Schober, Linda; Schaier, Matthias; Zeier, Martin; Spratte, Julia; Fluhr, Herbert; Steinborn, Andrea
Abstract : Problem: Recent studies revealed appropriate differentiation of recent thymic emigrant (RTE)‐regulatory T cells (Tregs) to be crucial for maintaining healthy pregnancy. Currently, the role of responder T cells (Tresps) is not known. Method of study: Six‐color flow cytometric analysis was used to detect differences in the differentiation of highly proliferative inducible co‐stimulatory (ICOS) + ‐RTE‐Tregs/Tresps and apoptosis‐sensitive ICOS − ‐RTE‐Tregs/Tresps into mature naïve (MN)‐, CD31 + ‐memory and CD31 − ‐memory Tregs/Tresps in women with spontaneous preterm labor (sPL) compared to healthy pregnancy. Results: Healthy pregnancy was characterized by an increased differentiation of ICOS + ‐ and ICOS − ‐RTE‐Tregs, as well as ICOS + ‐RTE‐Tresps via CD31 + ‐memory Tregs/Tresps into CD31 − ‐memory Tregs/Tresps. Women with sPL showed an early interruption of RTE‐Treg/Tresp differentiation. Instead, ICOS + ‐MN‐Tresps and partly ICOS − ‐MN‐Tregs differentiated into CD31 − ‐memory Tregs/Tresps, causing a significant reduction of both ICOS + ‐Tregs and ICOS + ‐Tresps, but an increase of ICOS − ‐Tresps within total CD4 + ‐T‐helper cells. Conclusion: Aberrant differentiation of ICOS + ‐T cells is associated with sPL.